2009
DOI: 10.1080/08941930802713043
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Suture Fixation on Mesh Contraction after Abdominal Hernia Repair

Abstract: Mesh contraction is a threat for hernia repair. Our aim is to analyze the effects of fixation techniques on mesh contraction. Forty-eight rats with abdominal wall defects were equally divided into four groups (G): G1 (control) with no repair, G2 defects were repaired with free polypropylene mesh, and G3 and G4 defects were reinforced with prolene mesh fixed by running and interrupted sutures, respectively. The corners of the defect and prolene mesh were marked with silver clips. The contraction rate was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The inversely influenced filament thickness on retraction is also important. Other studies reported significantly lower retraction rates (10) but with graft placement over the intact fascia. One of the most prominent researchers reports that the LWPP had lower retraction rates due to induction of weaker immune response (11), which is in keeping with our results.…”
Section: Discussionmentioning
confidence: 91%
“…The inversely influenced filament thickness on retraction is also important. Other studies reported significantly lower retraction rates (10) but with graft placement over the intact fascia. One of the most prominent researchers reports that the LWPP had lower retraction rates due to induction of weaker immune response (11), which is in keeping with our results.…”
Section: Discussionmentioning
confidence: 91%
“…Biological ACTM may possibly reduce the shrinkage on the basis of its repairing mechanism different from polypropylene mesh. e polypropylene mesh is nonabsorbent; thus, the repair relies on the contraction of scar tissue [5]. e ACTM degrades while tissue grows; thus, the repair makes the use of tissue regeneration [41].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mesh used in abdominal hernia repair is less suitable for the weak abdominal wall treatment. Based on the scar repair to tighten surrounding tissues, the classical polypropylene mesh results in the decrease of local abdominal wall compliance after healing and brings strong discomfort when patients move the waist [5]. Besides, the increasing risk of infection from effusion stimulated by exogenous polypropylene mesh and unsatisfied therapeutic improvement of abdominal muscle strength after polypropylene mesh implantation are in urgent need to be solved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that running suture technique, which provides more balanced tension around the mesh until its integration into adjacent healthy tissue, to be more useful for decreasing of mesh contraction (Sekmen et al 2009). The continuous suture pattern was used within the inlay technique, in which the breakdown of one stitch results in the dehiscence of the whole suture line.…”
Section: Figures In Parenthesis Indicatementioning
confidence: 99%